Power : a new social analysis - Russell, Bertrand ([S.l.] : Routledge, 1975)
The key to human nature that Marx found in wealth and Freud in sex, Bertrand Russell finds in power. Power, he argues, is man's ultimate goal, and is, in its many guises, the single most important element in the development of any society. Writting in the late 1930s when Europe was being torn apart by extremist ideologies and the world was on the brink of war, Russell set out to found a 'new science' to make sense of the traumatic events of the day and explain those that would follow. The result was Power , a remarkable book that Russell regarded as one of the most important of his long career. Countering the totalitarian desire to dominate, Russell shows how political enlightenment and human understanding can lead to peace - his book is a passionate call for independence of mind and a celebration of the instinctive joy of human life.